2000
DOI: 10.1007/s004210050669
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin acute reaction and haematological adaptations to short, intermittent hypobaric hypoxia

Abstract: This study aimed to determine whether brief hypoxic stimuli in a hypobaric chamber are able to elicit erythropoietin (EPO) secretion, and to effectively stimulate erythropoiesis in the short term. In two different experiments, a set of haematological, biochemical, haemorheological, aerobic performance, and medical tests were performed in two groups of healthy subjects. In the first experiment, the mean plasma concentration of EPO ([EPO]) increased from 8.7 to 13.5 mU.ml-1 (55.2%; P < 0.01) after 90 min of acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
96
5
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 39 publications
(51 reference statements)
13
96
5
3
Order By: Relevance
“…The paucity of experimental studies linking underwater experience with physiological diving capability is surprising, given the considerable attention devoted to the potential benefits of altitude hypoxia in boosting the body oxygen reserves of terrestrial mammals -especially humans (see Böning, 1997;Rodríguez et al, 2000). Exercise physiologists have repeatedly demonstrated that training at altitude increases Hct, Hb and serum erythropoietin levels (Mairbäurl, 1994;Klausen et al, 1996;Böning, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The paucity of experimental studies linking underwater experience with physiological diving capability is surprising, given the considerable attention devoted to the potential benefits of altitude hypoxia in boosting the body oxygen reserves of terrestrial mammals -especially humans (see Böning, 1997;Rodríguez et al, 2000). Exercise physiologists have repeatedly demonstrated that training at altitude increases Hct, Hb and serum erythropoietin levels (Mairbäurl, 1994;Klausen et al, 1996;Böning, 1997).…”
mentioning
confidence: 99%
“…There is also evidence that altitude hypoxia in combination with exercise is more potent in stimulating erythropoiesis than is hypoxia alone (Mairbäurl, 1994). In a more recent study, Rodríguez et al (2000) reported that brief, intermittent episodes of hypobaric hypoxia presented over a 3-week period were sufficient to stimulate erythropoiesis and boost red cell mass, Hct and Hb levels of humans. The effects of hypoxia conditioning on muscle oxygen reserves are equivocal, though Terrados et al (1990) observed increased Mb levels in human leg muscle following hypobaric hypoxic training.…”
mentioning
confidence: 99%
“…If RBC volume can be increased apart from a decrease in PV, then total blood volume could be increased and potentially enhance endurance performance following intermittent altitude exposures. However, given the unchanged [RBC] (24,25,70,72,80,88,104), whereas others (all from the same lab) have reported large increases in one or all of these parameters (19,86,87). The higher [Hb] and Hct reported in those studies (19,86,87) may be possible if there was also a large decrease in PV.…”
Section: "St-co T-t-+1mentioning
confidence: 89%
“…A recent study by Katayama et al (51) reported no change in V0 2ma x and HRmax, measured in hypobaric hypoxia, after lowlanders were exposed to 4,500 m for 1 h-d" for 7 d, but found a 5% increase in resting and maximal exercise Sa0 2 . Rodriguez et al (87) increase in exercise Sa0 2 , and a 22% increase in exercise VE, measured in hypobaric hypoxia, in lowlanders exposed to 5000 m for 2 h»d" 1 for 14 d. All of these studies on lowlanders suggest that resting intermittent exposures to high altitude induce a large degree of ventilatory acclimatization and some degree of hematological acclimatization. However, as in the studies on trained mountaineers, adequate measures of AMS and submaximal endurance performance were not made.…”
Section: Introductionmentioning
confidence: 94%
“…De este modo, la duración del programa o de la sesión puede modificar el grado de adaptación del individuo, siendo la duración mínima de la sesión para que esta sea un estímulo que supere el umbral de adaptación y produzca una reacción aguda de 90 min en los programas de IHE (Rodríguez et al, 2000) y de 60 min en los de IHT (Millet et al 2010). Hay que tener también en cuenta la frecuencia semanal, la altitud simulada o el tipo de hipoxia (hipobárica o normobárica), ya que son elementos que inciden en la variabilidad de los resultados y que deben de esclarecerse para una correcta aplicación de estos métodos (Millet el al., 2010).…”
Section: Discussionunclassified